Unravelling a food derived bioactive peptide with dual functionality of antimicrobial and immunomodulatory properties - MOHAN, NIAMH MAIRE (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Microbiology, 2020)
In this thesis, a computational data mining and feature based approach to unravel the abundance of unexplored peptides from nature and to identify potent, novel antimicrobial peptides (AMPs) from phyto-proteins is proposed. In the first section of this thesis, we explored Pisum sativum hydrolysed (PSH) protein and evaluated its potential as a bio-preservative. As the ?clean label? revolution takes hold, paired with increased consumer demand for natural products, alternative preserving solutions are needed to maintain food safety and limit spoilage. PSH offers an attractive plant-based solution, capable of reducing disease causing pathogens while being economically viable, and environmentally friendly. Expanding on the potential of the PSH, we identified NuriPep 1653, an individual peptide component of the hydrolysate with remarkable antimicrobial activity. AMPs are an integral part of every species contributing to host defense and have been lauded as contenders in combating the antibiotic crisis. Despite immense scientific efforts to bring antibiotic alternatives to the market, very few have been approved for market sale as they have yet to surpass the activity of traditional therapies. Paired with the reluctance from the pharmaceutical industry to financially support antimicrobial research, this means that the need for novel antimicrobial compounds has never been greater. We have explored the therapeutic potential of NuriPep 1653 against clinically relevant pathogens and highlighted its appeal for the pharmaceutical sector given its limited propensity for inducing resistance, rapid kill kinetics, non-toxic nature, ability to reverse resistance and synergise with conventional antibiotic therapies. Moreover, NuriPep 1653 reduced the activation of pathways and cytokines associated with pro-inflammatory response indicating its abilities to modulate the host immune response. This vastly expands the therapeutic potential of the peptide. Overall, we describe a novel discovery approach to identify AMPs encrypted within phyto-proteins. Through PSH and NuriPep 1653, we hope to expand on the current knowledge related to protein hydrolysates and AMPs and inch closer to providing novel antimicrobial solutions across the food and pharmaceutical industries.
APPROVED
Keywords: Antimicrobial peptides; Antimicrobial resistance; Data mined peptides; Food preservation; Acinetobacter baumannii; Protein hydrolysates